Satureja montana L. and Origanum majorana L. Decoctions: Antimicrobial Activity, Mode of Action and Phenolic Characterization - Gomes, Fernanda Isabel (2020)
Medicinal and aromatic plants are known to have a wide range of uses and health benefits, and should be exploited for their bioactivity. Here we evaluated the antimicrobial activity of decoctions of Satureja montana L. and Origanum majorana L. against Gram-positive and Gram-negative bacteria and Candida spp. as well as their mechanism of action and phenolic characterization. The Satureja montana and Origanum majorana extracts were effective against a broad set of species, including the Gram-positive Staphylococcus aureus, Enterococcus faecalis, and Streptococcus dysgalactiae and the Gram-negative Klebsiella pneumoniae and Pseudomonas aeruginosa. Both extracts were found to have rosmarinic acid as the main phenolic compound and to exert their antimicrobial activity at the level of the cell membrane. Membrane perturbations by the extracts impaired cell membrane integrity only a few hours after exposure. This study confirms the bioactive potential of Satureja montana and Origanum majorana decoctions, and supports the development of novel formulations with wide antimicrobial properties based on these medicinal and aromatic herbs.